Transcendental equation in quadratic form and its solution - Ahmed, Mostak; Hossain, Alamgir (Bangladesh Journal of Scientific and Industrial Research, 2012)
Not available DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11460 Bangladesh J. Sci. Ind. Res. 47(2), 239-242, 2012